Catalytic applications of composite aerogels - Suh, DJ (ELSEVIER SCIENCE BV, 2004)
Unitary and composite aerogels with high specific surface areas and pronounced mesoporosity have been prepared by the controlled sol-gel method and subsequent carbon dioxide supercritical drying and heat treatment. The aerogels were characterized by N-2 adsorption-desorption, thermal analyses (TGA-DTA), X-ray diffraction (XRD), temperature-programmed desorption (TPD), temperature-programmed reduction (TPR), infrared spectroscopy (IR), transmission electron microscopy (TEM), and reaction tests. The composite aerogels containing extremely small active metal particles showed strong metal-support or metal-metal interactions. The specific catalytic behaviours of aerogel catalysts are explained in terms of their unique textural and chemical properties. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: METAL-OXIDE AEROGELS; GEL SYNTHETIC ROUTE; CARBON; DEACTIVATION; TRANSITION